Will They Stay or Will They Go? International Graduate Students and Their Decisions to Stay or Leave the U.S. upon Graduation - Han, Xueying (PLoS One, 2015)
The U.S. currently enjoys a position among the world’s foremost innovative and scientifically advanced economies but the emergence of new economic powerhouses like China and India threatens to disrupt the global distribution of innovation and economic competitiveness. Among U.S. policy makers, the promotion of advanced education, particularly in the STEM (Science, Technology, Engineering and Mathematics) fields, has become a key strategy for ensuring the U.S.’s position as an innovative economic leader. Since approximately one third of science and engineering post-graduate students in the U.S. are foreign born, the future of the U.S. STEM educational system is intimately tied to issues of global competitiveness and American immigration policy. This study utilizes a combination of national education data, a survey of foreign-born STEM graduate students, and in-depth interviews of a sub-set of those students to explain how a combination of scientists’ and engineers’ educational decisions, as well as their experience in school, can predict a students’ career path and geographical location, which can affect the long-term innovation environment in their home and destination country. This study highlights the fact that the increasing global competitiveness in STEM education and the complex, restrictive nature of U.S. immigration policies are contributing to an environment where the American STEM system may no longer be able to comfortably remain the premier destination for the world’s top international students.